Making large single crystals of 2D MOFs - Dong, Renhao; Feng, Xinliang (Nature materials, 2021)
Linking π -conjugated, electron-deficient ligands into atomically precise large single crystals of conducting 2D metal–organic frameworks can allow the determination of intrinsic electrical conductivity and charge transport mechanism.